Post-Soviet Russia : a journey through the Yeltsin era - Medvedev, Roy Aleksandrovich, 1925- (Columbia University Press, 2000)
Roy Medvedev, one of the world's best-known Russian scholars and a former consultant to both Gorbachev and Yeltsin analyzes the main events that have transpired in the Russian federation since late August 1991. He looks at the plans that were meant to.